PENGGUNAAN MODEL ENHANCED AMERICAN SEBAGAI PENGEMBANGAN DARI MODEL BINOMIAL PADA PENENTUAN HARGA OPSI SAHAM KARYAWAN - , DARA PUSPITA ANGGRAENI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Employee Stock Options (ESO) differ from standard exchange-traded options. The three main differences in a valuation model for employee stock options : Vesting Period, Exit Rate and Non-Transferability. In this thesis, the model for valuing employee stock options discussed. This model called Enhanced American model are implement with a generalized binomial method